A Systematic Review Comparing Bone Graft Harvest From the Iliac Crest, Tibia, and Calcaneus Donor Sites in Foot and Ankle Surgery - Jose M. Iturregui MD; Alex M. Moses MD; Glenn G. Shi MD; Edward T. Haupt MD (Foot & Ankle Orthopaedics, 2022)
Category: Basic Sciences/Biologics; Other Introduction/Purpose: Bone autografts are frequently harvested for use in foot and ankle surgery. The gold standard harvest site is the iliac crest; however there is known morbidity with this harvest site. Alternative harvest sites include the tibia and calcaneus which are easily accessible for lower extremity surgery. Controversy exists regarding the osteogenic potential of autografts from each location. We performed a systematic review of the known data on cellular autografts from the iliac crest, tibia, and calcaneus focusing on the total cells harvested from each site as well as the presence of the critically important osteogenic osteoprogenitor cells. We also reviewed autograft volume, autograft consistency, surgical techniques, and the morbidities and complications associated with each bone autograft harvest location. Methods: In accordance with the PRISMA 2020 guidelines, a literature search of the PubMed, Cochrane Library, Web of Science, and Google databases from inception through January 2022 was performed. The search terms included: 'autograft,' 'bone graft,' 'foot and ankle surgery,' 'iliac crest,' 'tibia,' 'calcaneus,' reamer irrigator aspirator,' 'RIA,' 'mesenchymal cells,' 'osteoprogenitor cells,' 'quantity,' 'number,' 'amount,' 'yield,' 'concentration,' 'surface antigens,' 'surface markers,' 'CD markers.' Studies were included if autologous bone graft was harvested from the iliac crest, femur, tibia, or calcaneus and the cells in the harvest underwent histologic evaluation, quantification, or CD surface antigen identification. We included studies with bone graft as well as bone marrow aspirates used as samples. The nucleated cell and osteoprogenitor cell yield was recorded from each location; and MSC CD markers present at each harvest site were extracted from the eligible studies. Results: 13 studies met our inclusion criteria. Eight studies performed cell quantification from the harvest sites. Notably these studies only provide counting of total nucleated cells without specific identification of the osteoprogenitors. Colony-forming units were also reported and their findings are reviewed. Total cellular material was on average greatest in the iliac crest, with intermediate counts in the proximal tibia, and lowest in the calcaneus autograft samples. Five studies identified mesenchymal stromal cell (MSC) cluster of differentiation (CD) antigens at the harvest sites of interest. CD markers confirm osteoprogenitor cells are present in each sample location. Total number of osteoprogenitor cells remains unknown, however authors have attempted to extrapolate this number based on number of total nucleated cells and other data. Conclusion: Osteoprogenitor cells can be harvested from the iliac crest, tibia, and calcaneus. Greater total nucleated cell yields were identified in harvests from the iliac crest with descending amounts moving location distally in the limb. Nucleated cells were counted to provident estimates of osteoprogenitor cells yields in most studies, with flow cytometry confirmation that osteoprogenitors are present. Strict quantification of osteoprogenitor cells remains unknown. Multiple studies compared cellular material from bone marrow aspirates versus bone graft harvests themselves. Studies with modern techniques are needed to identify the true number of osteoprogenitors in each location.